2021
DOI: 10.3390/ijms22179224
|View full text |Cite
|
Sign up to set email alerts
|

Amelogenin-Derived Peptides in Bone Regeneration: A Systematic Review

Abstract: Amelogenins are enamel matrix proteins currently used to treat bone defects in periodontal surgery. Recent studies have highlighted the relevance of amelogenin-derived peptides, named LRAP, TRAP, SP, and C11, in bone tissue engineering. Interestingly, these peptides seem to maintain or even improve the biological activity of the full-length protein, which has received attention in the field of bone regeneration. In this article, the authors combined a systematic and a narrative review. The former is focused on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 169 publications
(301 reference statements)
1
7
0
Order By: Relevance
“…31 EMPs, including amelogenin which constitutes 90% of these proteins, promote the regeneration of cementum, periodontal ligament, and alveolar bone and are key proteins in periodontal tissue regeneration. [32][33][34] Recombinant human amelogenin (rhAm), a single component amelogenin obtained through genetic engineering, boasts advantages such as convenient acquisition and stable properties compared to EMPs extracted from animal tooth germs. 12 In our study, we found that rhAm could enhance hPDLCs proliferation and osteogenesis differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…31 EMPs, including amelogenin which constitutes 90% of these proteins, promote the regeneration of cementum, periodontal ligament, and alveolar bone and are key proteins in periodontal tissue regeneration. [32][33][34] Recombinant human amelogenin (rhAm), a single component amelogenin obtained through genetic engineering, boasts advantages such as convenient acquisition and stable properties compared to EMPs extracted from animal tooth germs. 12 In our study, we found that rhAm could enhance hPDLCs proliferation and osteogenesis differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The ECM (also matrisome) is a complex non-cellular three-dimensional macromolecular network present within all tissues and organs, forming the foundation on which cells sit. It is composed of 1. structural and specialized proteins (such as collagens, elastin, fibrillin, laminin, fibronectin, vitronectin, nidogen also known as entactin, tenascin, amelogenins, dentin sialoprotein, and dentin phosphoprotein), 2. glycosaminoglycans, also known as mucopolysaccharides (hyaluronan, heparin, heparan sulphate, chondroitin sulphate, keratan sulphate, and dermatan sulphate), which are the major components of proteoglycans (proteins that contain covalently linked glycosaminoglycans, such as syndecan, betaglycan, perlecan, aggrecan, decorin, andversican), 3. minerals (hydroxyapatite and derivatives found in bone or dentine), 4. lipids, 5. water, and 6. tissue-bound growth factors [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The most abundant proteins of the ECM are collagens [ 17 , 18 ].…”
Section: The Extracellular Matrixmentioning
confidence: 99%
“…When AMELX is secreted by ameloblasts to the outside of cells, it exists in the form of a monomer or nano aggregate. [ 43 , 44 , 187 , 188 ] The inside of nano aggregate is a hydrophobic core, and the outside is a hydrophilic retractable fragment. [ 189 , 190 , 191 , 192 ] In dependence on temperature, pH, and protein concentration, AMELX self‐assembles to form a linear morphology that provides nucleation sites for hydroxyapatite (Figure 5 ).…”
Section: Biomineralization Mechanismmentioning
confidence: 99%
“…Apoptosis of enamel‐forming cells at a later stage of development results in the failure of enamel regeneration, which is different from bone mineralization. [ 22 , 43 , 44 ] Bone formation also begins at the embryonic stage, during which mesenchymal cells aggregate to form a cohesive mass that approximates the shape and location of the bone. [ 45 , 46 , 47 ] Then, they differentiate into osteoblasts, osteoclasts, and osteocytes, which eventually participate in bone mineralization.…”
Section: Introductionmentioning
confidence: 99%